Fangirling Culture in X: a Virtual Ethnographic Study of Seventeen Boygroup Fans in Makassar City - Nabila Rahmayuni Saharuddin; Abdul Rahman (Gudang Jurnal Multidisiplin Ilmu, 2026)
This study explores the cultural practice of fangirling on social media platform X as a space for identity negotiation and communal solidarity in the digital era. Using a digital ethnography approach, data was collected through participant observation, in-depth interviews with fans, and a documentary study of the digital footprints of the informants. The results show that fangirling is not merely a form of passive consumption, but rather a communal cultural activity carried out massively and organized through fictitious kinship structures in cyberspace. This phenomenon manifests itself in the form of digital "work culture," such as the ritual of collectively streaming music and mobilizing votes to increase the symbolic capital of the idol group SEVENTEEN on the global stage. This practice confirms a shift in social interaction patterns, where group loyalty is bound by a commitment to the idol's aesthetics and achievements. Anthropologically, this activity creates a new value system that blurs the boundaries between the private space of fans and the digital public space, while simultaneously strengthening the position of social media platform X as a primary locus in the formation of contemporary popular culture.